Edge Detection Based on Biomimetic Pattern Recognition - Ning Chen; Xiao-ping Song; Yi Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper introduced a technique for edge detection by Biomimetic pattern recognition (BPR).  The images were scanned into a computer. Due to the nature of the acquiring technique, the acquired images have lots of artifacts, resulting in complicated edge detection.  According to this, we used Biomimetic pattern recognition, which is based on “matter cognition” instead of “matter classification” and rather closer to the function of the human being. Finally, the experiments showed that the technique is feasible and has some flexibility.